A study for the redevelopment of Muizenberg - Hockly, Anthony H (School of Architecture, Planning and Geomatics, 2020)
From being "South Africa's Premier Holiday Resort", Muizenberg today presents a picture of a depressed resort suburb. This Thesis will study the physical, social and economic characteristics of the area and by relating them to present and likely future patterns of social activity, identify the problems that beset the area and gauge Muizenberg's future as a holiday resort. The Thesis will then put forward proposals for the relief of these problems and present a redevelopment plan within the general framework of which detailed physical form could be planned.